Effects of Fish Waste Effluent on the Growth, Yield and Quality of Cucumis sativus L - Mohammad Moneruzzaman, Khandaker; Nornasuha, Yusoff; Nashriyah, Mat; Ellyzatul Ainah, Buang (2018)
This study was conducted to evaluate the potential effects of fish waste extract on the growth, yield and quality of cucumber which is a popular cucurbitaceae fruit vegetable. Different treatments were arranged according with CRD layouts with five replicates for each treatment. All the six (6) treatments viz; control, NPK, 10 ml, 20 ml, 40 ml and 50 ml of fish waste extract were applied to the potting media. The results showed that the application of 20 ml of fish waste extract increased the vine length, number of leaf, chlorophyll content (SPAD), stomatal conductance and leaf TSS content of cucumber compared to other treatments and control. Treatment with 50 mL of fish waste extract produced the highest leaf area. The chlorophyll concentration, carotene content, chlorophyll fluorescence and photosynthetic yield also positively affected with fish waste extracts. It was also found that number of flower, number of fruit, and weight of individual fruit of cucumber also significantly increased by fish waste extracts. It can be concluded that 20 ml fish waste extract was the best treatment for improving the growth, yield and quality of cucumber. Foliar application of fish waste effluent on Cucurbitaceae vegetables is merit to further study.